SYAIR LAGU DOLANAN ANAK-ANAK JAWA PADA MASYARAKAT JAWA TIMUR (KAJIAN STRUKTUR NARATIF ALBERT B.LORD) - Rian Damariswara , Ita Kurnia (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
The Javanese children's dolanan song in the East Java community has a pattern or formula that has not been studied. The formula, the basis of the poet to sing it in various versions. The formula possessed by the dolanan song, has similarities to Albert B.Lord's research. The purpose of the study is to describe the structure of the formula in the Javanese children's song dolanan song in the community of East Java. The theory used is the theory of the structure of Albert B. Lord's narrative. Research is qualitative. Data source in research is informant. Types of data collected ie java children song dolanan song in the community of East Java. Data collection techniques in research using observation, recording, interview and recording techniques. Data analysis techniques in research using content analysis and descriptive analysis. The results showed that the formula contained in the lyric of the dolanan songs of the children of East Java community, namely (1) the formula of row relationships is the formula of interrelationships between rows in the dolanan song. The formula is based on the relationship of word order, complete construction and ellipse, the same structure, the taxation, the exchange of parts at a particular position, and the substitution. (2) formula lines. The formula of the lines is the formula of each line that becomes the guidance in the preparation of the dolanan song. The formula, divided into line lengths, row patterns in the dolanan song lyrics, and sound elements in rows or purwakanthi